2020
DOI: 10.1021/acsbiomaterials.0c01254
|View full text |Cite
|
Sign up to set email alerts
|

Bioinspired Non-Immunogenic Multifunctional Sealant for Efficient Blood Clotting and Suture-Free Wound Closure

Abstract: Engineering bioinspired peptide-based molecular medicine is an emerging paradigm for the management of traumatic coagulopathies and inherent bleeding disorder. A hemostat-based strategy in managing uncontrolled bleeding is limited due to the lack of adequate efficacy and clinical noncompliance. In this study, we report an engineered adhesive peptide-based hybrid regenerative medicine, sealant 5, which is designed integrating the structural and functional features of fibrin and mussel foot-pad protein. AFM stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 57 publications
0
18
0
Order By: Relevance
“…Altogether, these data proved that SEAgel can not only efficiently stopped the bleeding but also may prevent the liver adhesion after surgery. To further prove the safety of the SEAgel, immunogenic response experiments were carried out following the previous report . The ELISA results showed that a very low IgG response was observed for SEAgel, which was not significantly different when compared to that of the commercially available Fibrin glue (Figure g).…”
Section: Resultsmentioning
confidence: 79%
See 4 more Smart Citations
“…Altogether, these data proved that SEAgel can not only efficiently stopped the bleeding but also may prevent the liver adhesion after surgery. To further prove the safety of the SEAgel, immunogenic response experiments were carried out following the previous report . The ELISA results showed that a very low IgG response was observed for SEAgel, which was not significantly different when compared to that of the commercially available Fibrin glue (Figure g).…”
Section: Resultsmentioning
confidence: 79%
“…To further prove the safety of the SEAgel, immunogenic response experiments were carried out following the previous report. 38 The ELISA results showed that a very low IgG response was observed for SEAgel, which was not significantly different when compared to that of the commercially available Fibrin glue (Figure 5g). The pro-inflammatory cytokine IFN-γ was also detected showing that SEAgel did not induce the over-expression of the cytokine, further demonstrating the good biocompatibility of SEAgel (Figure 5f).…”
Section: ■ Results and Discussionmentioning
confidence: 84%
See 3 more Smart Citations